Strategic Marketing Market-Oriented Corporate and Business Unit Planning - Tomczak, Torsten (Springer Fachmedien Wiesbaden : Gabler, 2018)
This textbook gives a clear and comprehensive overview of the process of strategic marketing planning. The authors provide a systematic framework that helps to structure the vast and complex marketing knowledge, thus making it more accessible and easier to use for strategic marketing planning. Many short case reports and examples serve to illustrate the key aspects of the marketing planning process. Contents The information basis of marketing planning Market-oriented corporate planning Market-oriented business unit planning Planning the marketing mix Marketing implementation and management control The authors Prof. Dr. Torsten Tomczak is Director of the Institute for Customer Insight at the University of St. Gallen (ICI-HSG) and Professor of Marketing at the University of St. Gallen. Prof. Dr. Sven Reinecke is Director of the Institute of Marketing at the University of St. Gallen (IfM-HSG).Prof. Dr. Alfred Kuss is Professor (em.) at the Marketing Department of Freie Universität Berlin.